Predictors, Morbidity, and Costs Associated with Pneumothorax during Electronic Cardiac Device Implantation. Issue 9 (29th June 2016) - KOTTER, JOHN; LOLAY, GEORGES; CHARNIGO, RICHARD; LEUNG, STEVE; MCKIBBIN, CHRISTOPHER; SOUSA, MATTHEW; JIMENEZ, LUIS; GURLEY, JOHN; BIASE, LUIGI DI; NATALE, ANDREA; SMYTH, SUSAN; DARRAT, YOUSEF; et al.
Abstract : Background: Pneumothorax (PTX) is a major cause of morbidity associated with cardiac implantable electronic devices (CIEDs). We sought to evaluate predictors of PTX at our centers during CIED implantations, including the venous access technique utilized, as well as to determine morbidity and costs associated with PTX. Methods: We reviewed records of all patients undergoing cardiac device implant or revision with new venous access at our institutions between 2008 and 2014. Common demographic and procedure characteristics were collected including age, sex, body mass index (BMI), comorbidities, and method of venous access (axillary vein vs classic proximal subclavian vein technique). Results: We identified 1, 264 patients who met criteria for our analysis, with a total of 21 PTX cases during CIED implantation. The strongest predictor for PTX was the venous access strategy: 0 of 385 (0%) patients with axillary vein approach versus 21 of 879 (2.4%) with traditional subclavian vein approach, P = 0.0006. Additional predictors of PTX included advanced age, female sex, low BMI, and a new device implant (vs device upgrade). The occurrence of PTX was associated with increased length of stay: 3.0 days (median; interquartile range [IQR] 3) versus 1.0 day (median; IQR: 1), P = 0.0001, with a cost increase of 361.4%. Conclusion: An axillary vein vascular access strategy was associated with greatly reduced risk of iatrogenic PTX versus the traditional subclavian approach for CIED placement. Similarly, device upgrade with patent vascular access carried less risk of PTX compared to new device implantation. PTX occurrence significantly prolonged hospitalization and increased costs.